تعليم المفردات للمبتدئين بالمدخل السياقي - Rizqi, Muhammad Rizal (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2025)
The aims of this study are, first: to produce the mufradat’s learning materials which developed based on contextual approach for student of “Fadllillah”. Second: to verify the developed mufradat’s learning materials effectiveness. Because it’s become the main reason of this developing this text book for many years, mufradat’s learning in this “Fadlillah” was used durusul lughah, but both of them cannot increase student’s achievement only and but also the interest study of student. The research method of this study is research and development by Borg and Gall’s model and the steps are research and information collecting, planning, develop preliminary, truth testing, field testing, product revision and final product revision. The result of this research are, first: the specification of developed learning materials are contained by: this materials learning only for beginner to learning Arabic language, the materials learning easily memorized, easily understood and easily for practiced in conversation about daily activities, the example, the exercise and the presentation matter of this materials learning has arranged systematically from easy matter to difficult matter, interactive presentation method which can make the students learn actively, in materials learning are various color and picture to easily student for understanding it. Second: learning mufradat’s by using this developed material learning can increase the result of mufradat’s learning and the interest of students effectively, it is not only shown by different degrees both students at before’s class and experiment’s class which counted by SPSS 22, but also by quisionare’s result which descripted that this materials learning is easy to understand and interest the students to read and learn it happily. These result of this research shows that the student have more interst in mufradat than before so they can understand the matters easily by using materials learning which developed by contextual approach.